E-062 Safety and efficacy of the pipeline embolization device for treatment of posterior circulation intracranial aneurysms. (23rd July 2017) - Almandoz, Delgado J; Kayan, Y; Scholz, J; Uittenbogaard, K; Milner, A; Fease, J; Wallace, A; Nelson, K; Mulder, M
Abstract : Purpose: To examine clinical and angiographic outcomes in a cohort of consecutive patients with posterior circulation intracranial aneurysms treated with the Pipeline Embolization Device (PED) at a referral center. Methods: We conducted a retrospective review of all patients with posterior circulation intracranial aneurysms treated with the PED in our center between January 23 rd, 2012 and January 24 th, 2017. Baseline patient and aneurysm characteristics, intra-operative, peri-operative and delayed complications were recorded. Aneurysm volumes in initial and follow-up angiographic studies were calculated using AngioCalc. Clinical outcomes were categorized using the modified Rankin Scale (mRS). Results: 17 patients underwent 18 PED procedures to treat 19 posterior circulation intracranial aneurysms during the study period. 12 patients were women (71%) and 5 men (29%). Mean age was 60 years (range 13-80 years). 16 patients were premedicated with aspirin/clopidogrel with VerifyNow testing (94%), and 1 with aspirin/ticagrelor without VerifyNow testing (6%). 8 aneurysms were incidental (42%), 5 symptomatic (26%, 2 from mass effect), 4 recurrent (21%) and 3 ruptured (16%). 6 aneurysms were fusiform (32%), 3 dissecting (16%) and 2 blister (11%). 7 aneurysms were located in the basilar trunk (37%), 4 in the posterior inferior cerebellar artery (21%), 2 in the superior cerebellar artery (10.5%), 2 in the posterior cerebral artery (10.5%), 2 in the vertebral artery (10.5%), 1 in the basilar tip (5%) and 1 in a basilar perforator artery (5%). Mean aneurysm size was 8.8mm (1.7-34mm), mean neck was 6.7mm (0.6-32.6mm), mean dome-to-neck ratio was 1.3 (0.2-2.9). 12 aneurysms were wide-neck (≥4mm, 63%). Mean number of PEDs deployed per aneurysm was 1.3. Adjunctive coiling was performed in 4 aneurysms (21%). There were 2 intra-operative (11%), 3 peri-operative (17%) and 1 delayed (5.6%) complications, none led to a disabling neurological deficit (mRS≥3). There was no treatment-related mortality. There were no post-operative aneurysm ruptures. Overall mortality was 5.9%. Angiographic follow-up was available in 15 aneurysms (79%, 3 follow-ups currently pending), with a mean time to last angiographic follow-up of 23.7 months (median 11 months, range 3.3-61.3 months). At last follow-up, 11 aneurysms were completely occluded (73%), 3 aneurysms had incomplete occlusion (20%, mean 59.2% volume reduction), and 1 aneurysm had volume increase (7%, 166% increase). The enlarging aneurysm was re-treated with parent artery sacrifice (7%). Conclusion: The PED is a safe and effective treatment for wide-neck posterior circulation intracranial aneurysms, with high long-term complete aneurysm occlusion rates, low re-treatment rates, and a low rate of major treatment-related complications. Disclosures: J. Delgado Almandoz: 2; C; Medtronic Neurovascular, Accriva Diagnostics. Y. Kayan: 2; C; Medtronic Neurovascular. J. Scholz: None. K. Uittenbogaard: None. A. Milner: None. J. Fease: None. A. Wallace: None. K. Nelson: None. M. Mulder: None.